2011
DOI: 10.1089/brain.2011.0032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ongoing, Intrinsic Activity of Neuronal Populations for Quantitative Neuroimaging of Functional Magnetic Resonance Imaging–Based Networks

Abstract: A primary objective in neuroscience is to determine how neuronal populations process information within networks. In humans and animal models, functional magnetic resonance imaging (fMRI) is gaining increasing popularity for network mapping. Although neuroimaging with fMRI-conducted with or without tasks-is actively discovering new brain networks, current fMRI data analysis schemes disregard the importance of the total neuronal activity in a region. In task fMRI experiments, the baseline is differenced away to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The concept of the majority of the brains energy not directly supporting function was challenged in 1998 with the finding, using 13 C MRS, that approximately 80% of cortical neuronal energy in the resting state was directly supporting neuronal signaling, as measured quantitatively with glutamate/glutamine cycling ( Sibson et al, 1998 ). Subsequently this result has been replicated repeatedly and extended to GABAergic signaling and glial metabolism ( Yu et al, 2017 ) in animals and humans as well as to independent electrical measurements of signaling ( Hyder and Rothman, 2010 ; Hyder et al, 2011 , 2013a ). In addition multiple studies have shown that it is consistent with measurements of signaling and energetics at the cellular level when scaled up to whole cortex ( Atwell and Laughlin, 2001 ; Yu et al, 2017 ).…”
Section: Basic Structure Of Standard Cognitive Models (Scm) and Theirmentioning
confidence: 67%
“…The concept of the majority of the brains energy not directly supporting function was challenged in 1998 with the finding, using 13 C MRS, that approximately 80% of cortical neuronal energy in the resting state was directly supporting neuronal signaling, as measured quantitatively with glutamate/glutamine cycling ( Sibson et al, 1998 ). Subsequently this result has been replicated repeatedly and extended to GABAergic signaling and glial metabolism ( Yu et al, 2017 ) in animals and humans as well as to independent electrical measurements of signaling ( Hyder and Rothman, 2010 ; Hyder et al, 2011 , 2013a ). In addition multiple studies have shown that it is consistent with measurements of signaling and energetics at the cellular level when scaled up to whole cortex ( Atwell and Laughlin, 2001 ; Yu et al, 2017 ).…”
Section: Basic Structure Of Standard Cognitive Models (Scm) and Theirmentioning
confidence: 67%
“…Because metabolic activity measured by FDG uptake reflects the cumulative energy consumption in steady states, while BOLD signal from fMRI reflects fast temporal fluctuation of physiologic factors such as blood flow, blood oxygenation, and cerebral metabolic rate of oxygen, the metabolic network provides distinct information from the functional network on fMRI as well as from the structural network disclosed on diffusion tensor imaging ( Di et al, 2012 ; Wehrl et al, 2013 ). Furthermore, network construction using neuronal activity-coupled metabolism found on FDG PET could take regional metabolic activities into account to disclose energy efficiency rather than only concentrate on the changes of fluctuating neural activities without considering absolute amount of regional perfusion or metabolism ( Hyder et al, 2011 ; Smith et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work combining measurements of M or R 2 ' with baseline blood flow and blood volume will potentially provide quantitative information about the dynamics of oxygen metabolism. This will include information on both the intrinsic evoked response studied here and also the baseline state of CMRO 2 that has been pursued in other studies (Griffeth, Perthen et al 2011, Hyder, Herman et al 2011). …”
Section: Discussionmentioning
confidence: 99%